2022
DOI: 10.1186/s13075-022-02867-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of immune cells from Behçet’s syndrome patients: the importance of IL-17-producing cells and antigen-presenting cells in the pathogenesis of Behçet’s syndrome

Abstract: Background Behçet’s syndrome (BS) is an immune-mediated disease characterized by recurrent oral ulcers, genital ulcers, uveitis, and skin symptoms. HLA-B51, as well as other genetic polymorphisms, has been reported to be associated with BS; however, the pathogenesis of BS and its relationship to genetic risk factors still remain unclear. To address these points, we performed immunophenotyping and transcriptome analysis of immune cells from BS patients and healthy donors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Transcriptomic studies have revealed an active NF-κB pathway in peripheral Th17 cells. Additionally, analysis techniques such as WGCNA and pathway enrichment have highlighted the activation of APCs in BD [ 11 , 129 ]. The expression of IL-27, both at the mRNA and protein levels, is found to be reduced in the PBMCs and serum of active BD patients.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Transcriptomic studies have revealed an active NF-κB pathway in peripheral Th17 cells. Additionally, analysis techniques such as WGCNA and pathway enrichment have highlighted the activation of APCs in BD [ 11 , 129 ]. The expression of IL-27, both at the mRNA and protein levels, is found to be reduced in the PBMCs and serum of active BD patients.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…1 The cause of BD has not been fully elucidated; however, there is a genetic predisposition associated with human leukocyte antigen (HLA) -B51 and various immune cells, and some exogenous and environmental factors are thought to be involved in its pathogenesis. 2,3 The prevalence of BD is relatively high in Mediterranean countries and East Asia, including Japan, and its estimated prevalence in Japan is reported as 13.5 out of 100 000 people. 1 Gastrointestinal (GI) findings, also known as intestinal BD, are important manifestations of BD.…”
Section: Introductionmentioning
confidence: 99%
“…Behçet's disease (BD) is a refractory systemic inflammatory disease characterized by a set of clinical manifestations, including recurrent oral and genital ulcers, uveitis, cutaneous lesions, and multisystem involvements 1 . The cause of BD has not been fully elucidated; however, there is a genetic predisposition associated with human leukocyte antigen (HLA) ‐B51 and various immune cells, and some exogenous and environmental factors are thought to be involved in its pathogenesis 2,3 . The prevalence of BD is relatively high in Mediterranean countries and East Asia, including Japan, and its estimated prevalence in Japan is reported as 13.5 out of 100 000 people 1 …”
Section: Introductionmentioning
confidence: 99%